Verapamil in affective disorders: a controlled, double-blind study - Höschl, C; Kozený, J (Biological psychiatry, 1989)
Eighty-six depressed inpatients were divided into four groups: patients in each of three groups were treated, respectively, with identical capsules of verapamil, amitriptyline, or placebo, whereas the fourth group was treated eclectically by the ward physician with so-called state-adjusted treatment (SAT). Each treatment period lasted 5 weeks. Psychopathology was assessed with the Hamilton Rating Scale for Depression, by the Zung self-rating scale, by the 100-mm analog scale, and by general clinical impression. Results indicated that amitriptyline and SAT were superior to verapamil or placebo. There was no significant difference between verapamil and placebo or between SAT and amitriptyline. This finding was more definitive in the homogeneous subgroup of 55 women with DSM-III diagnosis of Major depression. In addition, 12 manic inpatients (DSM-III) were treated orally with verapamil, 24 with neuroleptics, and 11 with both neuroleptics and lithium carbonate. The decline of their psychopathology, assessed by the Brief Psychiatric Rating Scale (BPRS) and general impression, was fully comparable. Using Analysis of Variance (ANOVA), the statistical difference among courses of psychopathology expressed as total BPRS scores reaches borderline significance in favor of verapamil. In contrast to neuroleptics, verapamil did not induce any sedative, hypnotic, or cataleptic effects, and was well tolerated.
Keywords: klinické zkoušky jako téma; dvojitá slepá metoda; verapamil; úzkostné poruchy; Random Allocation; Double-Blind Method; psychologické testy; bipolární porucha; Middle Aged; mužské pohlaví; Anxiety Disorders; Adult; depresivní poruchy; Psychological Tests; Bipolar Disorder; Clinical Trials as Topic; ženské pohlaví; psychotické poruchy; Humans; Verapamil; amitriptylin; náhodné rozdělení; Amitriptyline; lidé středního věku; Psychotic Disorders; dospělí; Female; Depressive Disorder; lidé; Male